Digital signal processors e-course - Torgaev, S. N. specialist in the field of electronics associate Professor of Tomsk Polytechnic University, candidate of physico-mathematical Sciences 1984- (TPU Moodle, 2016)
Today the majority of signals processing is performed in digital form. This processing is carried out in so-called digital processing systems. This course is aimed to the development of principles of the construction of digital analog signal processing systems. The main emphasis is on the design of digital filters and their implementation using digital microprocessors.